Cytotoxic Investigation of Cynara sibthorpiana - Khatab, A.M.; Haggag, E.G.; Grace, M.H. (Asian Journal of Chemistry, 2010)
Bioassay guided fractionation of the different extracts of Cynara sibthorpiana against L1210 mouse leukemia cell line, led to the isolation of twelve phenolic compounds identified as caffeic acid 1, esculetin 2, apigenin 3, luteolin 4, quercetin 5, apigenin 7-O-glucoside 7, apigenin 7-O-rutinoside (isorhoifolin) 8, luteolin 7-O-glucoside (cynaroside) 10, luteolin 7-O-rutinoside (scolymoside) 11, apigenin 7-O-rhamnoside 6, scutellarein 7-O-rhamnoside 9, and quercetin 7-O-glucoside 12. The last three flavonoid glycosides are reported in this species for the first time. Caffeic acid, quercetin and quercetin 7-O-glucoside showed significant activity compared to the other isolated compounds showing the importance of the free 3-OH group for the cytotoxic activity.